The relationship between neuroticism, role conflict, job-home demands and work-family conflict (WFC) : A case study of Uzma Engineering Sdn. Bhd. - Meor Rashydan, Abdullah (2014)
The purpose of this study is to examine the relationship between Neuroticism, Role Conflict, Job-Home Demand with Work Family Conflict. Besides that, this study also aims to identify the correlation between Neuroticism, Role Conflict, Job-Home Demand and their impact on the Work Family Conflict. In this study, Neuroticism, Role Conflict, Job-Home Demand will be as independent variables and Work Family Conflict as a dependent variable. The Neuroticism Questionnaire (Eysenck et al., 1985) is chosen to measure the Neuroticism while Role Conflict Questionnaire from Carlson et al., (2000) is used to measure Role Conflict among employees in an organization. For Job-Home Demand, the questionnaire by Van Veldhoven et al. (2002) and Peeters et al. (2005) is used and Work Family Conflict questionnaire is from Netemeyer et al. (1996). This study was focused to staffs of Uzma Engineering Sdn Bhd as the respondents. Samples of 92 were selected randomly using simple random sampling techniques. The survey response was analysed by using the Statistical Package for Social Sciences (SPSS) Version 17.0. Pearson Correlation coefficient was carried out to examine the relationship between Neuroticism, Role Conflict and Job-Home Demand towards Work Family Conflict and lastly Linear regression analysis is conducted to determine the influences of the independent variables towards Work Family Conflict as dependent variable. It was found that there is a significant relationship between Emotional Stress, Emotional Strain, Work to Family Role Conflict, Family to Work Role Conflict, Job Behavior Demand, Job Attitude Demand, Home Attitude Demand, Home Emotion Demand and Home Behavior Demand Work Family Conflict. Thus, based on the Linear Regression analysis result, it shows that Home Emotion Demand and Home Behavior Demand predicts Work Family Conflict more than Emotional Stress, Emotional Strain, Work to Family Role Conflict, Family to Work Role Conflict, Job Behavior Demand, Job Attitude Demand and Home Attitude Demand. Therefore, it is recommended that an organization should develop a better work-family policy and create a better workplace environment which is to promote a balance work and family culture. Further research in similar variables in the other sectors such as manufacturing and service sectors can be performed as the majority of the research are only focusing in one particular sectors only. This research provides valuable information for policy makers in organisation, particularly in Oil and Gas industry in understanding and formulating ways to increase work family enrichment and decrease work family conflict in an Eastern cultural context.